Design and test of a novel wheat drying oven based on the real-time utilization of diesel engine waste heat. Issue 1 (1st January 2019) - Sun, Yufeng; Guo, Xueying; Xu, Bo; Wang, Chun; Wang, Yapeng; Jiao, Youzhou; Li, Suiliang; Ying, Jilai; Liu, Xinping
Abstract: A small, novel wheat drying oven was designed, and tested in order to validate the possibility of recovering diesel engine waste heat as thermal energy. Prior to experiments, the theoretical probability was conducted, and it was confirmed that the thermal energy required for drying wheat could be satisfied by reusing the diesel engine waste heat. Three different experiment parameters, including air temperature, baffle angle, and drying time, were controlled to optimize the results. Based on the experiment data, the optimum temperature for drying wheat was 55°C, and the optimum baffle angle was 23.25°. The drying efficiency decreased as the drying temperature and drying time increased. The moisture content of wheat decreased from 26.0% to 20.0% with 55°C hot air when the proposed wheat drying oven was used. The test results demonstrated that the proposed oven could be made to work.